Laparoscopy for Rectal Cancer - Atallah, Chady; Efron, Jonathan E. (Clinics in Colon and Rectal Surgery, 2017)
It is evident that the use of laparoscopy in the management of rectal cancer has gained popularity in the last few years. It is still, however, not widely accepted as the standard of care. Multiple randomized trials have shown that short-term outcomes and perioperative morbidity and mortality of laparoscopic proctectomy are equivalent to open surgery. However, data regarding long-term oncologic outcomes are still scarce, with only a few randomized trials reporting similar outcomes in both laparoscopic and open group. A more recent trial failed to replicate those results in patients with locally advanced rectal cancer. In this article, we will look at the most recent evidence regarding the use of laparoscopy for patients with rectal cancer. We will also briefly discuss the different approaches and new minimally invasive techniques used in this field, and we will talk about the challenges facing the widespread adoption of laparoscopic surgery in the management of rectal cancer.
Keywords: laparoscopy; proctectomy; techniques; rectal cancer; oncologic outcomes